1993
DOI: 10.1177/030098589303000214
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Chordoma in Two Ferrets (Mustela putorius furo)

Abstract: Chord oma in human beings is an uncommon neopl asm arising from remnants o f the not ochord .' ? It has also been report ed in seve ral animal spec ies, including th e rat ,' 2.,. cat,' dog," m in k," and ferrc t. t-"'? In human being s, cho rdo mas arise pred om inantl y in the sacrococcygeal and sphenooccipita l areas ! In ferr ets, all repo rted cases have been seen at or near the ta il tip .1.6. ' 0 T he purpose of thi s pap er is to describe chordo mas arising in th e cervical spina l region of two ferret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 11 publications
1
46
0
Order By: Relevance
“…11 The etiology of mesothelioma in other species is unknown and considered spontaneous. 12 Spontaneous, or idiopathic, mesotheliomas have been documented in many species. 12,13 Spontaneous mesotheliomas are rarely reported in birds but have been diagnosed in chickens, a pheasant, a pigeon (Columba livia), and a ferruginous hawk (Buteo regalis).…”
Section: Discussionmentioning
confidence: 99%
“…11 The etiology of mesothelioma in other species is unknown and considered spontaneous. 12 Spontaneous, or idiopathic, mesotheliomas have been documented in many species. 12,13 Spontaneous mesotheliomas are rarely reported in birds but have been diagnosed in chickens, a pheasant, a pigeon (Columba livia), and a ferruginous hawk (Buteo regalis).…”
Section: Discussionmentioning
confidence: 99%
“…Ferret chordomas most often form as grossly visible masses caudal to the last vertebra, at the tip of the tail, or rarely in the cervical region. 12,39 There is only 1 report of a ferret developing a chordoma in the thoracic region. 27 Although tails were not evaluated histologically in this study, tail masses were not noted grossly.…”
Section: Discussionmentioning
confidence: 99%
“…7 Chordomas are the most common musculoskeletal neoplasm in ferrets, 2 but are rare in humans and other animals. 1,6,9,17 In ferrets, chordomas occur most commonly at the tip of the tail, 2 but they have also been reported in the cervical region in 2 previous cases 8,18 and the thoracic vertebrae in 1 case. 14 In humans, there are 3 recognized subtypes of chordoma: classic chordoma, chondroid chordoma, and chordoma with malignant spindle cell component (dedifferentiated).…”
mentioning
confidence: 98%
“…14 In humans, there are 3 recognized subtypes of chordoma: classic chordoma, chondroid chordoma, and chordoma with malignant spindle cell component (dedifferentiated). 7,13,18 It has been suggested that ferret chordomas may act as an animal model for the chondroid subtype of human chordoma. 7,18 Differentiation between classic and chondroid subtypes in humans is significant, as chondroid chordomas are associated with a survival rate 3 times greater than that of classic chordomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation